The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/v14091879
|View full text |Cite
|
Sign up to set email alerts
|

Chikungunya Virus Shedding in Semen: A Case Series

Abstract: Background: Chikungunya is a viral disease that is transmitted by mosquitoes. It is characterized by an acute onset of fever and severe arthralgia. Methods: We describe six cases of acute and post-acute chikungunya in which viral RNA was detected in semen. Conclusions: The most prolonged detection period was 56 days after illness onset. We attempted to cultivate positive semen samples, but virus isolation was unsuccessful in all cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…48,49 Moreover, the virus was found in the urine and semen of patients during infection, which is also suggestive of renal tropism. 50,51 Although the frequency of alterations was much lower for liver markers, they had a higher correlation than all the others, and better spatially organized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…48,49 Moreover, the virus was found in the urine and semen of patients during infection, which is also suggestive of renal tropism. 50,51 Although the frequency of alterations was much lower for liver markers, they had a higher correlation than all the others, and better spatially organized.…”
Section: Discussionmentioning
confidence: 99%
“…Fittingly, CHIKV is known to replicate in baby hamster kidney cells (BHK‐21 cells) and was found in urine samples, suggesting a possible viral replication in the kidney 48,49 . Moreover, the virus was found in the urine and semen of patients during infection, which is also suggestive of renal tropism 50,51 . Although the frequency of alterations was much lower for liver markers, they had a higher correlation than all the others, and better spatially organized.…”
Section: Discussionmentioning
confidence: 99%
“…Cultivating SARS-CoV-2 from specimen can prove the existence of live virus, however, application of virus isolation is limited by many factors [7] , [8] , [9] , [10] , [11] . qRT-PCR is the gold standard method widely used in many diagnostic laboratories in China for the etiological detection of SARS-CoV-2 [12] .…”
Section: Discussionmentioning
confidence: 99%
“…Several animal models of CHIKV infection have been developed [8][15-20] making it possible to characterize the infection and associated histopathological lesions of the spleen, liver, lymph nodes and muscle, and the development of peri-articular oedema in the acute phase of infection. Some models also allow the study of CHIKV chronic infection [18,[21][22][23][24] as it has been suggested to occur in humans [13,14,25]. A study on partially immunodeficient mice [16] identified fibroblasts of the dermis, muscle and joint capsule, muscle satellite cells, epithelial and endothelial cells of many organs such as liver, brain and spleen as CHIKV cellular targets during the acute phase.…”
Section: Introductionmentioning
confidence: 99%